2017
DOI: 10.1186/s12896-017-0374-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous long-term cytotoxicity monitoring in 3D spheroids of beetle luciferase-expressing hepatocytes by nondestructive bioluminescence measurement

Abstract: BackgroundThree-dimensional (3D) spheroids are frequently used in toxicological study because their morphology and function closely resemble those of tissue. As these properties are maintained over a long term, repeated treatment of the spheroids with a test object is possible. Generally, in the repeated treatment test to assess cytotoxicity in the spheroids, ATP assay, colorimetric measurement using pigments or high-content imaging analysis is performed. However, continuous assessment of cytotoxicity in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(46 reference statements)
3
10
0
Order By: Relevance
“…Nevertheless, post‐transfection ultrasound treatment at 240 min time interval showed significantly increased GFP expression on peripheral regions which suggests that ultrasound activated lipopolyplexes are an effective and safe carrier to target surface proliferating cell layers of a spheroid. [ 44 ] The results obtained with multicellular spheroid coincide with that observed with monolayer culture of SKOV‐3 cells.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, post‐transfection ultrasound treatment at 240 min time interval showed significantly increased GFP expression on peripheral regions which suggests that ultrasound activated lipopolyplexes are an effective and safe carrier to target surface proliferating cell layers of a spheroid. [ 44 ] The results obtained with multicellular spheroid coincide with that observed with monolayer culture of SKOV‐3 cells.…”
Section: Resultssupporting
confidence: 70%
“…We have also attempted to assess the effectiveness of ultrasound‐mediated transfection in the spheroid culture, which mimics in vivo tumor physiology to a greater extent. [ 44,45 ] There are different methods for harvesting spheroid however, its shape, size, and compactness depend mainly on cell–cell interactions and type of extracellular matrix. The harvesting medium was modified to have desired extracellular matrix characteristics for cells to encourage spheroid formation.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that the decrease of luminescence intensity of beetle luciferase expressed under the control of a constitutive promoter shows good agreement with cell viability determined by the neutral red uptake assay . Furthermore, it has been reported that beetle luciferases, including firefly luciferase from Photinus pyralis and click beetle luciferase from Pyrearinus termitilluminans (Emerald luciferase, ELuc), have been utilized for continuous long‐term cytotoxicity monitoring in three‐dimensional spheroids by repetitive non‐destructive bioluminescence measurements, by utilizing the high stability and permeability properties of their substrate, d ‐luciferin . On the other hand, endoplasmic reticulum (ER)‐targeted secretion‐type copepod luciferase from Gaussia princeps , in which the ER retention signal (Lys‐Asp‐Glu‐Leu; KDEL) is fused in‐frame to the extreme C‐terminus of GLuc (hereinafter referred to as GLuc‐KDEL), has been used for high‐sensitivity cytotoxicity monitoring by measuring the extracellular release of GLuc‐KDEL by damaged cells …”
Section: Introductionmentioning
confidence: 99%
“…However, because it is impossible to avoid the positional effect and to regulate the copy number of the reporter plasmid, clonal variations of the response monitored by luciferase occur. To resolve this issue, we use a mouse artificial chromosome (MAC) vector to generate stable cell lines expressing luciferase . The MAC vector is constructed by truncating a natural mouse chromosome at a site adjacent to the centromeric region, and it is possible to integrate multiple transgenes into the target sites of the multi‐integrase (MI) platform on the MAC (MI‐MAC) vector .…”
Section: Introductionmentioning
confidence: 99%
“…The MI-MAC has also been transferred into HepG2 cells to verify cytotoxicity levels via luciferase reporter assay [69]. The MI-HAC/MAC system can be used in various cell types and has successfully achieved the insertion of large GLVs such as PACs and BACs and multiple genes into the MI-HAC/ MAC [70][71][72]. Although limitations exist regarding the available drug-resistant genes for five GLVs loading onto the MI-HAC/MAC vector, this was solved by reusing the same drug-resistant genes by disrupting them with genome editing technology (Honma et al, 2017, unpublished data).…”
Section: Gene-loading Techniques For Hacs/macsmentioning
confidence: 99%